A convergence behavior of HDQ and GDQ methods to analyze vibration characteristics of different configurations of FGM beams. (2022) - Khinchi, Ashish; Sharma, Pankaj
Abstract: In this investigation, a convergence behavior of harmonic differential quadrature (HDQ) and generalized differential quadrature (GDQ) methods is presented. The vibration behavior of different types of functionally graded material (FGM) beams are taken into consideration. The four types of material distributions are considered i.e., isotropic, thickness FGM, axial FGM and bi-direction FGM beam. The clamped-clamped boundary condition is considered in this study. It can be revealed that both numerical methods give well convergence.